Apuntes fenomenológicos sobre el perdón. Conversaciones entre la fenomenología de Merleau-Ponty y el libro Los rendidos de José Carlos Agüero - Mansilla, Katherine (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2015)
This paper seeks to show the proximity between the phenomenologicalreflection that Merleau-Ponty presents in the article “The War Has Taken Place” (1945), and the stories of Jose Carlos Agüero, in his book, Los rendidos (The Surrendered) (2015). From a phenomenological perspective (pre-reflective), both authors describe the experience of pain, shame and forgiveness as the pursuit of freedom and justice. The text is divided into two parts. In the first part, we present discourses of justice which were established after the Peruvian armed conflict (1980-2000) and the need of exercising the phenomenological “epochè” in order to describe the feelings of terror and shame that underlie as background of this shared experience. In the second part, supported by Merleau Ponty’s concepts of intersubjectivity and historicity, we define freedom as the pursuit of justice, which can only be understood at the primordialaction of being in relation with others, from which we give meaning to the past.

El presente artículo quiere mostrar la proximidad entre la reflexión fenomenológica que Merleau-Ponty elabora en el artículo La guerra tuvo lugar (1945), y los relatos de José Carlos Agüero, en su obra, Los Rendidos (2015). Desde una perspectiva fenomenológica (pre-reflexiva), ambos autores describen la experiencia del dolor, la vergüenza y el perdón como la búsqueda de libertad y justicia. El texto se divide en dos partes. En la primera parte, describimos los discursos de justicia instaurados luego del conflicto armado interno y la necesidad de realizar la “époje”, para describir los sentimientos de terror y vergüenza, que subyacen como fondo de esta vivencia compartida. En el segunda parte, apoyados en el conceptos de intersubjetividad e historicidad de Merleau-Ponty, definimos la libertad como la búsqueda de justicia, que solo puede comprenderse en la acción primordial de relación con los otros, a partir de la cual le damos sentido al pasado.
Keywords: Fenomenología; Maurice Merleau-Ponty; José Carlos Agüero; Intersubjetividad; Historicidad; https://purl.org/pe-repo/ocde/ford#6.03.01